Environmental challenges on aquaculture rearing in Malaysia: the views of brackish-water cage entrepreneurs in Malaysia - Idris, Khairuddin; Azman, Azmariana; Alby, Jeffrey Lawrence D'Silva; Man, Norsida; Mohamed Shaffril, Hayrol Azril (Marsland Press, 2014)
The main aim of this study is to investigate the environmental challenges’ – changing climate and natural disasters affect on aquaculture activities in Malaysia. Four in depth interviews have been conducted with five brackish-water cage entrepreneurs from four different locations in Peninsular Malaysia. Based on the findings of this study, four main environmental challenges have been identified to post formidable challenges on aquaculture activities in Malaysia, namely temperature rise, heavy rainfall, flood and water current. Further analyses have shown that these four environmental challenges have affected the socio-economic routines of the brackish-water cage entrepreneurs. A number of discussions and recommendations have been highlighted and hopefully they can assist the relevant parties in constructing a better strategy to face the future environmental challenges.